Impact of ATM location on its profi tability in Malopolskie and Podkarpackie provinces - Gurgul, Henryk; Suder, Marcin (Managerial Economics, 2019)
The fi rst decade of the 21st century saw a dynamic development in ATM networks. This was refl ected in the growth of the number of ATMs and number of withdrawals. However, in the beginning of the second decade, a slowdown in the dynamic development of this part of the banking system has been observed in Poland. The signifi cant reduction of interchange (which is the main source of revenue for ATM network deployers) and growing availability of cashless payments tempered a further intensive development of these networks. Over the next 3 years, this regression was refl ected in the declining number of withdrawals from ATMs and the insignifi cant growth of the number of ATMs. Therefore, ATM owners are forced to search for new solutions that could guarantee more profi ts. One way is the suitable choice of locations for new ATMs and removal of ATMs from non-profi table locations. In this paper, the authors have attempted to indicate the locations with the largest number of withdrawals on the basis of the number of withdrawals from the ATMs of the one of the largest ATM network deployers. The ATMs with the largest number of withdrawals are sources of the largest profi ts due to interchange. The authors have also indicated those locations where ATMs can be a source of losses.